Coaxial calcium-silicon-based bioactive wire as well as preparation method and application thereof

By covering the shell of calcium-silicon-based bioactive material on the degradable polymer core layer and using natural biomaterial matrix to enhance adhesion, the problems of complex preparation process and degraded mechanical properties in the prior art are solved, and the effect of simplifying production and improving bioactive and mechanical properties is achieved.

CN119701056AActive Publication Date: 2025-03-28BEIJING BEST LIFE REGENERATIVE MEDICINE TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411906120.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

In the prior art, when preparing polymer fibers, the process is complicated, the production cycle is long, and it is difficult to ensure the load of bioactive glass; at the same time, the direct blending of bioactive glass with polydopamine and polylactic acid spinning liquid will lead to a decrease in the mechanical properties of the fibers.

Method used

The structure of a coaxial calcium-silicon-based bioactive silk material is adopted. By covering the shell of the calcium-silicon-based bioactive material on the degradable polymer core layer, and using natural biomaterial matrix to enhance adhesion, simplify the production process, and improve bioactivity and mechanical properties.

Benefits of technology

The production process is simplified, the bioactivity and mechanical properties are improved, the problem of degradation of the mechanical properties of polymer fibers is solved, and the load capacity of calcium-silicon-based bioactive materials is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701056A_ABST
    Figure CN119701056A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical materials and the technical field of regenerative medicine, and particularly relates to a coaxial calcium-silicon-based bioactive wire as well as a preparation method and application thereof. The coaxial calcium-silicon-based bioactive wire comprises a degradable polymer core layer and a calcium-silicon-based bioactive material shell layer, the calcium-silicon-based bioactive material shell layer comprises a natural biological material matrix and calcium-silicon-based bioactive material particles, and the natural biological material matrix is composed of one or more of natural polysaccharide and dopamine. The degradable polymer core material is coated with a layer of calcium-silicon-based bioactive material, and the calcium-silicon-based bioactive material is adhered to the surface of the degradable polymer core material by virtue of a natural biological material, so that the degradable polymer is endowed with good biological activity and biocompatibility; and the problem of poor mechanical property of the calcium-silicon-based bioactive material fiber is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomedical materials and regenerative medicine, and specifically relates to a coaxial calcium-silicon-based bioactive silk material and a preparation method and application thereof. Background Art

[0002] Medical wires are widely used in the medical field. Medical wire materials include common metal materials such as nickel-titanium, cobalt-chromium, stainless steel, and molybdenum wire, which are often used in instrument parts. In addition, medical wire materials also include polymer wires, especially degradable polymer wires, which can be used in absorbable surgical sutures and bone filling materials. After being prepared into films, they can be used as wound dressings and anti-adhesion films. However, polymer wires lack biological activity and cannot promote tissue regeneration and repair. They also have poor adhesion to cells and poor biocompatibility.

[0003] Calcium-silicon-based bioactive materials, including bioactive ceramics and bioactive glass, are the only known bioactive materials that can chemically bond with bone tissue and soft tissue, and have good biocompatibility. Bioactive glass contains essential elements for the human body, such as calcium, phosphorus, silicon, and oxygen. When in contact with body fluids, it releases a large number of active ions, and mineralizes on its surface and damaged tissues to form a three-dimensional hydroxyapatite scaffold structure, which is conducive to the orderly climbing and growth of cells; the release of active ions can induce cell differentiation, proliferation and gene expression, and promote tissue regeneration.

[0004] Existing technologies utilize the good adhesion and biocompatibility of polydopamine to compound degradable polymers with bioactive glass to improve the bioactivity of degradable polymers. For example, there is a technology that uses an electrospinning process to prepare polymer fibers, and then immerses the polymer fibers in a dopamine solution. Dopamine self-polymerizes on the fiber surface to form polydopamine. The polymer fibers modified with polydopamine on the surface are immersed in a bioactive glass solution again, and the bioactive glass is adhered to the fiber surface by utilizing the adhesion of polydopamine. Another technology modifies the surface of bioactive glass with polydopamine, and directly adds it to a polylactic acid electrospinning solution to obtain a mixed spinning solution, which is then prepared into a composite fiber by electrospinning technology.

[0005] However, in the process of implementing the above prior art, the inventors found that there are at least the following problems:

[0006] The method of multiple impregnation of polymer fibers is complicated, has a long production cycle, and is difficult to ensure the loading amount of bioactive glass; direct blending of bioactive glass modified with polydopamine with polylactic acid spinning solution will lead to a decrease in the mechanical properties of polylactic acid fibers.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] In view of the above-mentioned deficiencies in the prior art, one purpose of the present invention is to provide a coaxial calcium-silicon-based bioactive filament, which is coated with a layer of calcium-silicon-based bioactive material on the outside of a degradable polymer core material. The calcium-silicon-based bioactive material relies on natural biological materials to adhere to the surface of the degradable polymer core material, which not only gives the degradable polymer good bioactivity and biocompatibility, but also solves the problem of poor mechanical properties of calcium-silicon-based bioactive material fiber filaments.

[0009] Another object of the present invention is to provide a preparation method and application of the coaxial calcium-silicon-based bioactive filament. The composite calcium-silicon-based bioactive filament is obtained by one-piece coaxial spinning, which simplifies the production process and saves production costs.

[0010] The technical solution of the present invention is:

[0011] In a first aspect, a coaxial calcium-silicon-based bioactive filament comprises: a degradable polymer core layer and a calcium-silicon-based bioactive material shell layer, wherein the calcium-silicon-based bioactive material shell layer comprises a natural biomaterial matrix and calcium-silicon-based bioactive material particles, and the natural biomaterial matrix is ​​composed of one or more of natural polysaccharides and dopamine.

[0012] Further, the degradable polymer core layer is composed of one or more of polylactide, polyglycolide-lactide copolymer, polycaprolactone, polyglycolic acid, polyvinyl alcohol, and polyhydroxyalkanoate;

[0013] and / or, the molecular weight of the degradable polymer used in the degradable polymer core layer is 10,000 to 150,000;

[0014] And / or, the natural polysaccharide includes cellulose, chitin, chitosan, chondroitin sulfate, and seaweed polysaccharide;

[0015] And / or, the calcium-silicon-based bioactive material particles are composed of one or more of bioactive ceramics, bioactive glass, regenerated silicon, calcium phosphosilicate and their derivatives.

[0016] Furthermore, the diameter of the degradable polymer core layer is 1 μm to 1 mm;

[0017] and / or, the thickness of the calcium-silicon-based bioactive material shell layer is 500 nm to 500 μm;

[0018] And / or, in the calcium-silicon-based bioactive material shell layer, the mass percentage of calcium-silicon-based bioactive material particles is 0.1% to 60%.

[0019] Furthermore, the diameter of the degradable polymer core layer is 5 μm to 760 μm;

[0020] And / or, the thickness of the calcium-silicon-based bioactive material shell layer is 800nm ​​to 250μm;

[0021] And / or, in the calcium-silicon-based bioactive material shell layer, the mass percentage of calcium-silicon-based bioactive material particles is 1% to 35%.

[0022] In a second aspect, a method for preparing the coaxial calcium-silicon-based bioactive filament as described in the first aspect comprises the following steps:

[0023] (1) preparing a degradable polymer core layer solution: dissolving a degradable polymer in an organic solvent and mixing the mixture uniformly to obtain the degradable polymer core layer solution;

[0024] (2) preparing a shell solution containing calcium-silicon-based bioactive material particles: first dissolving a natural biomaterial matrix in a suitable solvent, mixing uniformly, to obtain a natural biomaterial matrix solution, then adding calcium-silicon-based bioactive material particles to the natural biomaterial matrix solution, mixing uniformly, to obtain the shell solution containing calcium-silicon-based bioactive material particles;

[0025] (3) The degradable polymer core layer solution obtained in step (1) and the shell layer solution containing calcium-silicon-based bioactive material particles obtained in step (2) are respectively injected into a core layer solution syringe and a shell layer solution syringe, and coaxial wet spinning is performed with the aid of a coaxial needle, and then anhydrous ethanol is selected as a coagulation bath and / or drying is performed for solidification to obtain the calcium-silicon-based bioactive filament.

[0026] Furthermore, the concentration of the degradable polymer core layer solution in step (1) is 0.05 g / mL to 0.50 g / mL;

[0027] and / or, the concentration of the natural biomaterial matrix solution in step (2) is 0.025 g / mL to 1.50 g / mL;

[0028] And / or, the particle size of the calcium-silicon-based bioactive material particles in step (2) is 20 nm to 80 μm.

[0029] Furthermore, the concentration of the degradable polymer core layer solution in step (1) is 0.05 g / mL to 0.40 g / mL;

[0030] and / or, the concentration of the natural biomaterial matrix solution in step (2) is 0.025 g / mL to 1.20 g / mL;

[0031] And / or, the particle size of the calcium-silicon-based bioactive material particles in step (2) is 20 nm to 50 μm.

[0032] Furthermore, the organic solvent in step (1) is one or a mixture of ethyl acetate, dichloromethane, acetone, 1,4-dioxane, N-methylpyrrolidone, chloroform, tetrahydrofuran, hexafluoroisopropanol, acetonitrile, and dichloroacetic acid;

[0033] And / or, the coaxial wet spinning technology in step (3) is to inject the degradable polymer core layer solution and the shell layer solution containing calcium-silicon-based bioactive material particles through an injection head to obtain the coaxial calcium-silicon-based bioactive filament structure, and the injection head is a coaxial needle having a coaxially arranged inner channel and outer channel.

[0034] Further, the degradable polymer core layer solution is injected at an injection speed of 40 μL / min to 10 mL / min; further, the injection speed of the degradable polymer core layer solution is 100 μL / min to 6 mL / min;

[0035] And / or, the shell solution containing calcium-silicon-based bioactive material particles is injected at an injection speed of 10 μL / min to 5 mL / min; further, the shell solution containing calcium-silicon-based bioactive material particles is injected at an injection speed of 40 μL / min to 2 mL / min;

[0036] And / or, the drying temperature in step (3) is 35°C to 45°C; further, the drying temperature is 35°C to 40°C;

[0037] And / or, the drying in step (3) is vacuum drying, the vacuum drying time is 8h to 72h, and the vacuum degree is -0.1MPa to 0.1MPa; further, the vacuum drying time is 12h to 48h, and the vacuum degree is -0.08MPa to 0.06MPa.

[0038] In the third aspect, an axolotl calcium silicate-based bioactive silk material as described in the first aspect or the axolotl calcium silicate-based bioactive silk material as described in the second aspect is used in the fields of absorbable surgical sutures, bone filling, wound dressings, and anti-adhesion membranes.

[0039] Compared with the prior art, the present invention has the following advantages:

[0040] (1) The coaxial calcium-silicon-based bioactive filament provided by the present invention combines a core layer biodegradable polymer with a shell layer calcium-silicon-based bioactive material, and adds natural biomaterials such as natural polysaccharides to enhance the adhesion between the two, thereby improving the shortcomings of the biodegradable polymer, which lacks bioactivity and poor biocompatibility, and at the same time solves the problem of poor mechanical properties of calcium-silicon-based bioactive material fiber filaments;

[0041] (2) The calcium-silicon-based bioactive filament provided by the present invention is a coaxial filament structure in which a core layer is covered by a shell layer, and the calcium-silicon-based bioactive material is quantitatively distributed on the surface of the degradable polymer, which will not destroy the mechanical properties of the polymer filament and has excellent tensile strength and flexibility;

[0042] (3) The coaxial injection head and wet spinning technology provided by the present invention can accurately control the diameter and thickness of the core layer and the shell layer, as well as the amount of calcium-silicon-based bioactive material. The production process is simple, the conditions are mild, the operation is easy, the energy consumption is low, the cost is low, and large-scale continuous production can be achieved;

[0043] (4) The coaxial calcium-silicon-based bioactive silk material provided by the present invention has important application advantages in multiple fields such as absorbable surgical sutures, bone filling, wound dressings, and anti-adhesion membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0045] Figure 1 Schematic diagram of coaxial needle spinning. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described below in conjunction with examples. The embodiments of the present invention are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and processes are given. It should be clear to those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention, and the protection scope of the present invention is not limited to the following embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention.

[0047] In the present invention, the endpoints and any values ​​of the disclosed ranges are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in the present invention.

[0048] An embodiment of the present invention provides a coaxial calcium-silicon-based bioactive filament, which comprises: a degradable polymer core layer and a calcium-silicon-based bioactive material shell layer; the calcium-silicon-based bioactive material shell layer contains a natural biomaterial matrix and calcium-silicon-based bioactive material particles; the natural biomaterial matrix is ​​composed of one or more of natural polysaccharides and dopamine.

[0049] In the above technical solution, the coaxial calcium-silicon-based bioactive filament combines the degradable polymer as the core layer with the calcium-silicon-based bioactive material as the shell layer to form a core-shell structure, which improves the biocompatibility of the degradable polymer in the core layer and gives it cell activity; at the same time, the core layer provides mechanical support for the shell layer to exert biological activity. Natural biomaterials such as natural polysaccharides are also added to the shell layer to enhance the adhesion between the degradable polymer and the calcium-silicon-based bioactive material, further improving the shortcomings of the degradable polymer's lack of bioactivity and poor biocompatibility. The calcium-silicon-based bioactive material is quantitatively distributed on the surface of the degradable polymer, which will not destroy the mechanical properties of the polymer filament and has excellent tensile strength and flexibility. Coaxial calcium-silicon-based bioactive filaments can be used in many scenarios. They can be used as absorbable surgical sutures, can be used for bone filling, and can be woven into wound dressings and anti-adhesion membranes.

[0050] In the above coaxial calcium-silicon-based bioactive filament, as an optional embodiment, the degradable polymer core layer is composed of one or more of polylactide, polyglycolide-lactide copolymer, polycaprolactone, polyglycolic acid, polyvinyl alcohol, and polyhydroxyalkanoate;

[0051] And / or, the molecular weight of the degradable polymer used in the degradable polymer core layer is 10,000 to 150,000 (such as 10,000, 20,000, 30,000, 40,000, 50,000, 60,000, 70,000, 80,000, 90,000, 100,000, 110,000, 120,000, 130,000, 140,000 and any numerical range);

[0052] And / or, the natural polysaccharide includes cellulose, chitin, chitosan, chondroitin sulfate, seaweed polysaccharide, etc.;

[0053] And / or, the calcium-silicon-based bioactive material particles are composed of one or more of bioactive ceramics, bioactive glass, regenerated silicon, calcium phosphosilicate and their derivatives.

[0054] In the above technical solution, although the calcium-silicon-based bioactive material particles have the characteristics of hydration and self-solidification, the hydration and self-solidification requires a long reaction time, and the activity of the bioactive material will be lost in this process, because the hydration and self-solidification is caused by the mineralization process of the calcium-silicon-based bioactive material, and the mineralization process will release calcium and phosphorus active ions, and form hydroxyapatite after mineralization, but the original activity will be greatly lost. Therefore, by adding a natural biomaterial matrix to the shell layer of the calcium-silicon-based bioactive material, the adhesion of the natural biomaterial matrix such as natural polysaccharides is used to adhere the calcium-silicon-based bioactive material particles to the degradable polymer core layer.

[0055] The regenerated silicon mentioned in the present invention can be prepared according to the method described in the patent application with publication number CN111017934A, or the commercially available regenerated silicon produced by Beijing Xingfu Yisheng High-tech Co., Ltd. can be used. Any type of regenerated silicon of this product can be used in the present invention. The material has a porous scaffold structure formed by the accumulation of nano-scale silica particles, and calcium and phosphorus elements uniformly distributed in the scaffold, and is a biologically active calcium phosphosilicate compound; the specific surface area of ​​the regenerated silicon is 200-350㎡ / g. The regenerated silicon of the present invention can also be a POSS-based regenerative medical material prepared according to the method described in the publication number CN109771692A, which is a polyhedral cage structure composed of Si-O-Si bonds in silicon oxide as a framework, and calcium and phosphorus elements are embedded therein. The regenerated silicon of the present invention can also be prepared according to the method described in the patent application with patent number CN110101904B.

[0056] In the above-mentioned coaxial calcium-silicon-based bioactive filament, as an optional embodiment, the diameter of the degradable polymer core layer is 1 μm to 1 mm (for example, 3 μm, 8 μm, 15 μm, 50 μm, 100 μm, 250 μm, 500 μm, 750 μm, 900 μm); further optionally, the diameter of the degradable polymer core layer is 5 μm to 760 μm (for example, 10 μm, 25 μm, 50 μm, 80 μm, 120 μm, 250 μm, 400 μm, 600 μm, 750 μm);

[0057] In the above-mentioned coaxial calcium-silicon-based bioactive filament, as an optional embodiment, the thickness of the calcium-silicon-based bioactive material shell layer is 500nm to 500μm (for example, 550nm, 750nm, 1μm, 5μm, 10μm, 50μm, 100μm, 200μm, 400μm); further optionally, the thickness of the calcium-silicon-based bioactive material shell layer is 800nm ​​to 250μm (for example, 950nm, 1.5μm, 4μm, 12μm, 35μm, 60μm, 100μm, 200μm);

[0058] In the above-mentioned coaxial calcium-silicon-based bioactive filaments, as an optional embodiment, in the calcium-silicon-based bioactive material shell layer, the mass percentage of calcium-silicon-based bioactive material particles is 0.1% to 60% (for example, 1%, 1.5%, 3%, 5%, 10%, 15%, 20%, 25%, 35%, 40%, 60%); further optionally, the mass percentage of calcium-silicon-based bioactive material particles is 1% to 35% (for example, 2%, 4%, 12%, 18%, 24%, 30%). The mass percentage of calcium-silicon-based bioactive material particles has a greater influence on the mechanical properties. Within this range, the calcium-silicon-based bioactive material particles can be evenly distributed in the shell layer, and the shell layer has better mechanical strength.

[0059] The method for preparing the above-mentioned coaxial calcium-silicon-based bioactive filament comprises the following steps:

[0060] (1) preparing a degradable polymer core layer solution: dissolving the degradable polymer in an organic solvent, and mixing evenly, such as continuously stirring, until the polymer is completely dissolved, to obtain the degradable polymer core layer solution;

[0061] (2) preparing a shell solution containing calcium-silicon-based bioactive material particles: first dissolving one or more of natural polysaccharides (including cellulose, chitin, chitosan, chondroitin sulfate, seaweed polysaccharides, etc.) and dopamine in a suitable solvent, for example, dissolving cellulose, chitin, and chitosan in a NaOH / urea mixed aqueous solution (or using directly water-soluble carboxymethyl cellulose, carboxymethyl chitosan, etc.), dissolving chondroitin sulfate, seaweed polysaccharides, and dopamine in water, and dissolving dopamine in a Tris-HCl buffer solution, and mixing them uniformly, such as continuously stirring until they are completely dissolved, to obtain a natural biomaterial matrix solution, and then adding the calcium-silicon-based bioactive material particles to the natural biomaterial matrix solution, and stirring and mixing them uniformly to obtain the shell solution containing the calcium-silicon-based bioactive material particles;

[0062] (3) The degradable polymer core layer solution obtained in step (1) and the shell layer solution containing calcium-silicon-based bioactive material particles obtained in step (2) are respectively injected into a core layer solution syringe and a shell layer solution syringe, and coaxial wet spinning is performed with the aid of a coaxial needle, and then anhydrous ethanol is selected as a coagulation bath and / or drying is performed for solidification to obtain the calcium-silicon-based bioactive filament.

[0063] In the above technical scheme, anhydrous ethanol can be selected as a coagulation bath for shaping. During the process of immersing in a coagulation bath for coagulation and shaping, some gaps will be generated between the materials, which will cause some hole structures of the calcium-silicon-based bioactive silk. After shaping, it will be dried and the hole structure will be retained; it can also be directly dried and shaped. If it is not immersed in a coagulation bath and directly dried, these hole structures will not be generated, and the diameter of the silk will be small. In the present invention, the curing method can be selected according to the specific conditions of the silk, such as the diameter requirements and the good shape of the fiber. If the required silk diameter is large, the anhydrous ethanol coagulation bath + drying method can be selected for shaping, which is helpful for maintaining the shape of the coaxial fiber. If there is no coagulation bath, the coaxial fiber shape may be difficult to maintain. If the required silk diameter is small, the drying method can be directly used for shaping, so that the solvent evaporates quickly, the silk will shrink severely, and therefore directly become very small. In addition, when using a coagulant, in order to meet the maintenance of the coaxial fiber shape, the coagulant cannot dissolve the shell layer, and anhydrous ethanol is the most suitable as a coagulant. In the present invention, when anhydrous ethanol is used as a coagulant for shaping, the wire needs to be left standing in the anhydrous ethanol for a certain period of time, generally 2 to 8 hours to completely shape it, usually 2 hours to basically shape it, and the 2 to 8 hours of standing time has little effect on the mechanical properties of the wire.

[0064] As an optional embodiment, the concentration of the degradable polymer core layer solution in step (1) is 0.05 g / mL to 0.50 g / mL (e.g., 0.08 g / mL, 0.10 g / mL, 0.12 g / mL, 0.15 g / mL, 0.20 g / mL, 0.25 g / mL, 0.30 g / mL, 0.35 g / mL, 0.40 g / mL, 0.45 g / mL). The core layer within this range can provide sufficient mechanical support for the shell layer. A concentration that is too low cannot provide mechanical support for the shell layer, and a concentration that exceeds this value makes fiber extrusion more difficult; further optionally, the concentration of the degradable polymer core layer solution is 0.05 g / mL to 0.40 g / mL (e.g., 0.08 g / mL, 0.10 g / mL, 0.13 g / mL, 0.16 g / mL, 0.18 g / mL, 0.20 g / mL, 0.25 g / mL, 0.30 g / mL, 0.35 g / mL, 0.37 g / mL).

[0065] As an optional embodiment, the organic solvent in step (1) is one or a mixture of ethyl acetate, dichloromethane, acetone, 1,4-dioxane, N-methylpyrrolidone, chloroform, tetrahydrofuran, hexafluoroisopropanol, acetonitrile, and dichloroacetic acid. The core layer solvent can be used as long as it can dissolve the degradable polymer, evaporates completely during the drying process, and does not affect the mechanical properties.

[0066] As an optional embodiment, the concentration of the natural biomaterial matrix solution in step (2) is 0.025g / mL to 1.50g / mL (for example, 0.05g / mL, 0.08g / mL, 0.12g / mL, 0.20g / mL, 0.35g / mL, 0.50g / mL, 0.80g / mL, 1.0g / mL, 1.20g / mL, 1.40g / mL); further optionally, the concentration of the natural biomaterial matrix solution is 0.025g / mL to 1.20g / mL (for example, 0.05g / mL, 0.08g / mL, 0.11g / mL, 0.15g / mL, 0.18g / mL, 0.25g / mL, 0.30g / mL, 0.40g / mL, 0.60g / mL, 1.10g / mL).

[0067] As an optional embodiment, the particle size of the calcium-silicon-based bioactive material particles in step (2) is 20nm~80μm (for example, 30nm, 80nm, 150nm, 350nm, 500nm, 800nm, 1μm, 5μm, 10μm, 30μm, 50μm, 75μm); further optionally, the particle size of the calcium-silicon-based bioactive material particles is 20nm~50μm (for example, 30nm, 80nm, 150nm, 350nm, 600nm, 750nm, 1.2μm, 3μm, 8μm, 12μm, 20μm, 35μm, 45μm).

[0068] As an optional embodiment, the coaxial wet spinning technology in step (3) is to inject the degradable polymer core layer solution and the shell layer solution containing calcium-silicon-based bioactive material particles through an injection head to obtain the coaxial calcium-silicon-based bioactive filament structure, and the injection head is a coaxial needle with a coaxially arranged inner channel and outer channel (such as Figure 1 As shown). The wire diameter is determined by the core layer diameter and the shell layer thickness. The core layer diameter and the shell layer thickness are affected by the diameter of the injection head and the size of the inner and outer channels separated axially, as well as the injection speed. Finally, the final wire diameter, core layer diameter and shell layer thickness are obtained after solidification and / or drying in the solidification bath. Generally speaking, in terms of the structural size of the injection head, the larger the diameter of the inner channel, the larger the core layer diameter; the closer the outer channel at the tip of the injection head is to the inner channel, that is, the smaller the shell layer outlet spacing, the smaller the shell layer thickness; in terms of injection speed, when the core layer injection speed is the same, the slower the shell layer speed, the larger the shell layer thickness; when the shell layer injection speed is the same, the faster the core layer speed, the smaller the shell layer thickness, because the core layer speed is greater than the shell layer, which has a stretching effect on the shell layer. The faster the core layer speed, the more obvious the stretching effect, and the thinner the shell layer is pulled; in terms of drying volatile solvents, the larger the solution concentration of the shell layer and / or the core layer, the smaller the shrinkage degree, and the thicker the wire diameter.

[0069] As an optional embodiment, the degradable polymer core layer solution is injected at an injection speed of 40 μL / min to 10 mL / min (e.g., 60 μL / min, 80 μL / min, 100 μL / min, 250 μL / min, 500 μL / min, 800 μL / min, 1 mL / min, 2.5 mL / min, 5 mL / min, 8 mL / min); further optionally, the injection speed of the degradable polymer core layer solution is 100 μL / min to 6 mL / min (e.g., 150 μL / min, 250 μL / min, 350 μL / min, 450 μL / min, 550 μL / min, 750 μL / min, 1.2 mL / min, 2 mL / min, 2.5 mL / min, 3 mL / min, 4 mL / min, 5.5 mL / min);

[0070] As an optional embodiment, the shell solution containing calcium-silicon-based bioactive material particles is injected at an injection speed of 10 μL / min to 5 mL / min (e.g., 20 μL / min, 40 μL / min, 50 μL / min, 100 μL / min, 400 μL / min, 600 μL / min, 1 mL / min, 2 mL / min, 3 mL / min, 4 mL / min); further optionally, the injection speed of the shell solution containing calcium-silicon-based bioactive material particles is 40 μL / min to 2 mL / min (e.g., 50 μL / min, 60 μL / min, 75 μL / min, 1.2 mL / min, 2 mL / min, 2.5 mL / min, 3 mL / min, 4 mL / min, 5.5 mL / min);

[0071] As an optional embodiment, the drying temperature in step (3) is 35°C to 45°C (for example, 36°C, 38°C, 40°C, 42°C, 44°C); further optionally, the drying temperature is 35°C to 40°C (for example, 36°C, 37°C, 38°C, 39°C); the upper limit of the drying temperature cannot exceed the tolerance temperature of the degradable polymer, for example, the glass transition temperature of polylactic acid is around 55°C, so the maximum drying temperature should not exceed 45°C.

[0072] As an optional embodiment, the drying in step (3) is vacuum drying, the vacuum drying time is 8h to 72h (e.g., 12h, 18h, 24h, 30h, 48h, 54h, 60h, 70h), and the vacuum degree of the vacuum drying is -0.1MPa to 0.1MPa (e.g., -0.08MPa, -0.05MPa, -0.03MPa, -0.01MPa, 0.01MPa, 0.03MPa, 0.05MPa , 0.08MPa); further optionally, the vacuum drying time is 12h~48h (for example, 16h, 20h, 24h, 32h, 36h, 45h), and the vacuum degree of the vacuum drying is -0.08MPa~0.06MPa (for example, -0.06MPa, -0.04MPa, -0.02MPa, -0.015MPa, 0MPa, 0.015MPa, 0.02MPa, 0.04MPa, 0.05MPa).

[0073] The embodiment of the present invention also provides the use of the coaxial calcium-silicon-based bioactive silk material in the fields of absorbable surgical sutures, bone fillings, wound dressings, and anti-adhesion membranes.

[0074] The present invention is further illustrated by the following examples, but the present invention is not limited to these examples.

[0075] The recycled silicon used in the following examples or comparative examples is a commercially available product from Beijing Xingfu Yisheng High-tech Co., Ltd.

[0076] Example 1

[0077] A coaxial calcium-silicon-based bioactive filament comprises a coaxial degradable polymer core layer and a calcium-silicon-based bioactive material shell layer, wherein the degradable polymer core layer is composed of polylactide having a molecular weight of 30,000 to 50,000; the calcium-silicon-based bioactive material shell layer comprises a natural biomaterial matrix and calcium-silicon-based bioactive material particles, wherein the natural biomaterial matrix is ​​composed of carboxymethyl chitosan, and the calcium-silicon-based bioactive material particles are composed of recycled silicon and have a mass percentage of 1.0% in the calcium-silicon-based bioactive material shell layer. For other parameters, see Table 1.

[0078] The preparation method thereof comprises the following steps:

[0079] (1) Preparation of polylactide core layer solution: 2 g of polylactide was added to 20 mL of 1,4-dioxane and stirred at 40° C. until dissolved;

[0080] (2) preparing a shell solution containing regenerated silicon particles: taking 5 g of carboxymethyl chitosan and adding it to 20 mL of water, stirring at room temperature until it is completely dissolved, then adding 0.05 g of regenerated silicon particles with a particle size of 20 to 500 nm, and stirring and mixing evenly;

[0081] (3) The polylactide core layer solution and the shell layer solution containing regenerated silicon particles were respectively injected into the syringe. With the help of a coaxial needle, the polylactide core layer solution was injected into the anhydrous ethanol coagulation bath at a rate of 100 μL / min, and the shell layer solution containing regenerated silicon particles was injected into the anhydrous ethanol coagulation bath at a rate of 80 μL / min. The two solutions met at the tip of the coaxial needle, and the shell layer solution containing regenerated silicon particles was wrapped around the outside of the polylactide core layer solution. After entering the anhydrous ethanol, it was gradually solidified and formed. After standing in the anhydrous ethanol for 2 hours, it was placed in a vacuum drying oven at 37°C and dried for 48 hours. The vacuum degree of the vacuum drying oven was 0.01 MPa, and the coaxial regenerated silicon bioactive filaments were obtained.

[0082] Example 2

[0083] A coaxial calcium-silicon-based bioactive filament, which is mainly different from Example 1 in that the degradable polymer core layer is composed of polylactide with a molecular weight of 100,000 to 150,000.

[0084] The preparation method thereof comprises the following steps:

[0085] (1) Preparation of polylactide core layer solution: 2 g of polylactide was added to 20 mL of dichloromethane and stirred continuously at 40° C. until dissolved;

[0086] (2) preparing a shell solution containing regenerated silicon particles: taking 5 g of carboxymethyl chitosan and adding it to 20 mL of water, stirring at room temperature until it is completely dissolved, then adding 0.05 g of regenerated silicon particles with a particle size of 20 to 500 nm, and stirring and mixing evenly;

[0087] (3) The polylactide core layer solution and the shell layer solution containing regenerated silicon particles were respectively injected into the syringe. With the help of a coaxial needle, the polylactide core layer solution was injected into the anhydrous ethanol coagulation bath at a rate of 100 μL / min, and the shell layer solution containing regenerated silicon particles was injected into the anhydrous ethanol coagulation bath at a rate of 80 μL / min. The two solutions met at the tip of the coaxial needle, and the shell layer solution containing regenerated silicon particles was wrapped around the outside of the polylactide core layer solution. After entering the anhydrous ethanol, it was gradually solidified and formed. After standing in the anhydrous ethanol for 8 hours, it was placed in a vacuum drying oven at 37°C and dried for 48 hours. The vacuum degree of the vacuum drying oven was 0.01 MPa, and the coaxial regenerated silicon bioactive filaments were obtained.

[0088] Example 3

[0089] A coaxial calcium-silicon-based bioactive filament, which is mainly different from Example 1 in that it has a high content of degradable polymer.

[0090] The preparation method thereof comprises the following steps:

[0091] (1) Preparation of polylactide core layer solution: 4 g of polylactide was added to 20 mL of chloroform and stirred at 40° C. until dissolved;

[0092] (2) preparing a shell solution containing regenerated silicon particles: taking 5 g of carboxymethyl chitosan and adding it to 20 mL of water, stirring at room temperature until it is completely dissolved, then adding 0.05 g of regenerated silicon particles with a particle size of 20 to 500 nm, and stirring and mixing evenly;

[0093] (3) The polylactide core layer solution and the shell layer solution containing regenerated silicon particles were respectively injected into the syringe. With the help of a coaxial needle, the polylactide core layer solution was injected into the anhydrous ethanol coagulation bath at a rate of 100 μL / min, and the shell layer solution containing regenerated silicon particles was injected into the anhydrous ethanol coagulation bath at a rate of 80 μL / min. The two solutions met at the tip of the coaxial needle, and the shell layer solution containing regenerated silicon particles was wrapped around the outside of the polylactide core layer solution. After entering the anhydrous ethanol, it was gradually solidified and formed. After standing in the anhydrous ethanol for 8 hours, it was placed in a vacuum drying oven at 37°C and dried for 48 hours. The vacuum degree of the vacuum drying oven was 0.01 MPa, and the coaxial regenerated silicon bioactive filaments were obtained.

[0094] Example 4

[0095] A coaxial calcium-silicon-based bioactive wire, which is mainly different from Example 1 in that the mass percentage of the calcium-silicon-based bioactive material particles in the calcium-silicon-based bioactive material shell is 4.8%.

[0096] The preparation method thereof comprises the following steps:

[0097] (1) Preparation of polylactide core layer solution: 2 g of polylactide was added to 20 mL of dichloromethane and stirred continuously at 50° C. until dissolved;

[0098] (2) preparing a shell solution containing regenerated silicon particles: taking 5 g of carboxymethyl chitosan and adding it to 20 mL of water, stirring at room temperature until it is completely dissolved, then adding 0.25 g of regenerated silicon particles with a particle size of 20 to 500 nm, stirring and mixing evenly;

[0099] (3) The polylactide core layer solution and the shell layer solution containing regenerated silicon particles were respectively injected into the syringe. With the help of a coaxial needle, the polylactide core layer solution was injected into the anhydrous ethanol coagulation bath at a rate of 100 μL / min, and the shell layer solution containing regenerated silicon particles was injected into the anhydrous ethanol coagulation bath at a rate of 80 μL / min. The two solutions met at the tip of the coaxial needle, and the shell layer solution containing regenerated silicon particles was wrapped around the outside of the polylactide core layer solution. After entering the anhydrous ethanol, it was gradually solidified and formed. After standing in the anhydrous ethanol for 8 hours, it was placed in a vacuum drying oven at 37°C and dried for 48 hours. The vacuum degree of the vacuum drying oven was 0.01 MPa, and the coaxial regenerated silicon bioactive filaments were obtained.

[0100] Example 5

[0101] A coaxial calcium-silicon-based bioactive filament, which is mainly different from Example 1 in that the degradable polymer core layer is composed of polylactide-glycolide with a molecular weight of 30,000-50,000, and the natural biomaterial matrix is ​​composed of dopamine.

[0102] The preparation method thereof comprises the following steps:

[0103] (1) Preparation of polylactide-glycolide core layer solution: 2 g of polylactide-glycolide was added to 20 mL of 1,4-dioxane and stirred at 50° C. until dissolved;

[0104] (2) preparing a shell solution containing regenerated silicon particles: taking 5 g of dopamine and adding it to 20 mL of water, stirring at room temperature until it is completely dissolved, then adding 0.05 g of regenerated silicon particles with a particle size of 20 to 500 nm, stirring and mixing evenly;

[0105] (3) The polylactide-glycolide core layer solution and the shell layer solution containing regenerated silicon particles were respectively injected into a syringe. With the help of a coaxial needle, the polylactide-glycolide core layer solution was injected into an anhydrous ethanol coagulation bath at a rate of 100 μL / min, and the shell layer solution containing regenerated silicon particles was injected into an anhydrous ethanol coagulation bath at a rate of 80 μL / min. The two solutions met at the tip of the coaxial needle, and the shell layer solution containing regenerated silicon particles was wrapped around the outside of the polylactide-glycolide core layer solution. After entering the anhydrous ethanol, it was gradually solidified and formed. After standing in the anhydrous ethanol for 8 hours, it was placed in a vacuum drying oven at 37°C and dried for 48 hours. The vacuum degree of the vacuum drying oven was 0.01 MPa, and the coaxial regenerated silicon bioactive filaments were obtained.

[0106] Example 6

[0107] A coaxial calcium-silicon-based bioactive filament, which is different from Example 1 mainly in that the calcium-silicon-based bioactive material particles are composed of bioactive glass 45S5.

[0108] The preparation method thereof comprises the following steps:

[0109] (1) Preparation of polylactide core layer solution: 2 g of polylactide was added to 20 mL of 1,4-dioxane and stirred at 50° C. until dissolved;

[0110] (2) Preparation of a shell solution containing 45S5 particles: 5 g of carboxymethyl chitosan was added to 20 mL of water and stirred at room temperature until completely dissolved. Then, 0.05 g of bioactive glass 45S5 particles with a particle size of 20 to 500 nm were added and stirred to mix evenly.

[0111] (3) The polylactide core layer solution and the shell layer solution containing bioactive glass 45S5 particles were respectively injected into the syringe. With the help of a coaxial needle, the polylactide core layer solution was injected into the anhydrous ethanol coagulation bath at a rate of 100 μL / min, and the shell layer solution containing regenerated silicon particles was injected into the anhydrous ethanol coagulation bath at a rate of 80 μL / min. The two solutions met at the tip of the coaxial needle, and the shell layer solution containing regenerated silicon particles was wrapped around the outside of the polylactide core layer solution. After entering the anhydrous ethanol, it gradually solidified and formed. After standing in the anhydrous ethanol for 8 hours, it was placed in a vacuum drying oven at 37°C and dried for 48 hours. The vacuum degree of the vacuum drying oven was 0.01 MPa, and the coaxial calcium-silicon-based bioactive filaments were obtained.

[0112] Example 7

[0113] A coaxial calcium-silicon-based bioactive filament, which is mainly different from Example 1 in that the injection speed of the core layer solution is different during preparation.

[0114] The preparation method thereof comprises the following steps:

[0115] (1) Preparation of polylactide core layer solution: 2 g of polylactide was added to 20 mL of 1,4-dioxane and stirred at 50° C. until dissolved;

[0116] (2) preparing a shell solution containing regenerated silicon particles: taking 5 g of carboxymethyl chitosan and adding it to 20 mL of water, stirring at room temperature until it is completely dissolved, then adding 0.05 g of regenerated silicon particles with a particle size of 20 to 500 nm, and stirring and mixing evenly;

[0117] (3) The polylactide core layer solution and the shell layer solution containing regenerated silicon particles were respectively injected into a syringe. With the help of a coaxial needle, the polylactide core layer solution was injected into an anhydrous ethanol coagulation bath at a rate of 500 μL / min, and the shell layer solution containing regenerated silicon particles was injected into an anhydrous ethanol coagulation bath at a rate of 80 μL / min. The two solutions met at the tip of the coaxial needle, and the shell layer solution containing regenerated silicon particles was wrapped around the outside of the polylactide core layer solution. After entering the anhydrous ethanol, it was gradually solidified and formed. After standing in the anhydrous ethanol for 8 hours, it was placed in a vacuum drying oven at 37°C and dried for 48 hours. The vacuum degree of the vacuum drying oven was 0.01 MPa, and the coaxial regenerated silicon bioactive filaments were obtained.

[0118] Example 8

[0119] A coaxial calcium-silicon-based bioactive filament, which is mainly different from Example 1 in that the injection speed of the shell solution during preparation is different.

[0120] The preparation method thereof comprises the following steps:

[0121] (1) Preparation of polylactide core layer solution: 2 g of polylactide was added to 20 mL of 1,4-dioxane and stirred at 50° C. until dissolved;

[0122] (2) preparing a shell solution containing regenerated silicon particles: taking 5 g of carboxymethyl chitosan and adding it to 20 mL of water, stirring at room temperature until it is completely dissolved, then adding 0.05 g of regenerated silicon particles with a particle size of 20 to 500 nm, and stirring and mixing evenly;

[0123] (3) The polylactide core layer solution and the shell layer solution containing regenerated silicon particles were respectively injected into a syringe. With the help of a coaxial needle, the polylactide core layer solution was injected into an anhydrous ethanol coagulation bath at a rate of 100 μL / min, and the shell layer solution containing regenerated silicon particles was injected into an anhydrous ethanol coagulation bath at a rate of 40 μL / min. The two solutions met at the tip of the coaxial needle, and the shell layer solution containing regenerated silicon particles was wrapped around the outside of the polylactide core layer solution. After entering the anhydrous ethanol, it was gradually solidified and formed. After standing in the anhydrous ethanol for 8 hours, it was placed in a vacuum drying oven at 37°C and dried for 48 hours. The vacuum degree of the vacuum drying oven was 0.01 MPa, and the coaxial regenerated silicon bioactive filaments were obtained.

[0124] Example 9

[0125] A coaxial calcium-silicon-based bioactive filament comprises a coaxial degradable polymer core layer and a calcium-silicon-based bioactive material shell layer, wherein the degradable polymer core layer is composed of polylactide having a molecular weight of 10,000 to 15,000; the calcium-silicon-based bioactive material shell layer comprises a natural biomaterial matrix and calcium-silicon-based bioactive material particles, wherein the natural biomaterial matrix is ​​composed of carboxymethyl chitosan, and the calcium-silicon-based bioactive material particles are composed of recycled silicon, and the mass percentage of the calcium-silicon-based bioactive material particles in the calcium-silicon-based bioactive material shell layer is 9.1%. For other parameters, see Table 1.

[0126] The preparation method thereof comprises the following steps:

[0127] (1) Preparation of polylactide core layer solution: 1 g of polylactide was added to 20 mL of 1,4-dioxane and stirred continuously at 40° C. until dissolved;

[0128] (2) preparing a shell solution containing regenerated silicon particles: taking 0.5 g of carboxymethyl chitosan and adding it to 20 mL of water, stirring at room temperature until it is completely dissolved, then adding 0.05 g of regenerated silicon particles with a particle size of 20 to 500 nm, stirring and mixing evenly;

[0129] (3) The polylactide core layer solution and the shell layer solution containing the regenerated silicon particles were respectively injected into a syringe, and the polylactide core layer solution and the shell layer solution containing the regenerated silicon particles were directly extruded into filaments at a rate of 100 μL / min and 80 μL / min, respectively, by means of a coaxial needle, and dried at 45°C to form filaments. Since the filaments are not squeezed into a coagulation bath and a direct drying method is adopted, the solvent evaporates very quickly and the filaments will shrink severely, so filaments with very small diameters will be directly obtained.

[0130] Example 10

[0131] A coaxial calcium-silicon-based bioactive filament comprises a coaxial degradable polymer core layer and a calcium-silicon-based bioactive material shell layer, wherein the degradable polymer core layer is composed of polylactide having a molecular weight of 30,000 to 50,000; the calcium-silicon-based bioactive material shell layer comprises a natural biomaterial matrix and calcium-silicon-based bioactive material particles, wherein the natural biomaterial matrix is ​​composed of dopamine, and the calcium-silicon-based bioactive material particles are composed of recycled silicon, and the mass percentage of the calcium-silicon-based bioactive material particles in the calcium-silicon-based bioactive material shell layer is 33.3%. For other parameters, see Table 1.

[0132] The preparation method thereof comprises the following steps:

[0133] (1) Preparation of polylactide core layer solution: 4 g polylactide was added to 10 mL 1,4-dioxane and stirred at 40° C. until dissolved;

[0134] (2) preparing a shell solution containing regenerated silicon particles: taking 20 g of dopamine and adding it to 20 mL of water, stirring at room temperature until it is completely dissolved, then adding 10 g of regenerated silicon particles with a particle size of 20 to 500 nm, stirring and mixing evenly;

[0135] (3) The polylactide core layer solution and the shell layer solution containing regenerated silicon particles were respectively injected into a syringe. With the help of a coaxial needle, the polylactide core layer solution was injected into an anhydrous ethanol coagulation bath at a rate of 4 mL / min, and the shell layer solution containing regenerated silicon particles was injected into an anhydrous ethanol coagulation bath at a rate of 2 mL / min. The two solutions met at the tip of the coaxial needle, and the shell layer solution containing regenerated silicon particles was wrapped around the outside of the polylactide core layer solution. After entering the anhydrous ethanol, it was gradually solidified and formed. After standing for 8 hours, it was placed in a vacuum drying oven at 39°C and dried for 12 hours. The vacuum degree of the vacuum drying oven was 0.05 MPa, and the coaxial regenerated silicon bioactive filaments were obtained.

[0136] Comparative Example 1

[0137] A coaxial calcium-silicon-based bioactive filament, which differs from Example 8 only in that, in step (3), a water coagulation bath is used instead of an anhydrous ethanol coagulation bath, and the rest of the settings are the same as Example 8. During the preparation process, it was found that after the two solutions met at the tip of the coaxial needle, the shell solution containing the regenerated silicon particles was wrapped around the outside of the polylactide core solution, but after entering the coagulant water, it gradually diffused and partially dissolved in the water, and the shell was lost.

[0138] Comparative Example 2

[0139] A calcium-silicon-based bioactive filament, which has only a shell layer but no core layer compared to the coaxial calcium-silicon-based bioactive filament in the embodiment, is specifically as follows: it is composed of a calcium-silicon-based bioactive material comprising a natural biomaterial matrix and calcium-silicon-based bioactive material particles, the natural biomaterial matrix is ​​composed of carboxymethyl chitosan, the calcium-silicon-based bioactive material particles are composed of recycled silicon, and the mass percentage of the calcium-silicon-based bioactive material is 1.0%. For other parameters, please see Table 1.

[0140] The preparation method thereof comprises the following steps:

[0141] (1) preparing a solution containing regenerated silicon particles: taking 5 g of carboxymethyl chitosan and adding it to 20 mL of water, stirring at room temperature until it is completely dissolved, then adding 0.05 g of regenerated silicon particles with a particle size of 20 to 500 nm, and stirring and mixing evenly;

[0142] (2) The solution containing the regenerated silicon particles was injected into an anhydrous ethanol coagulation bath at a rate of 80 μL / min. After entering the anhydrous ethanol, it gradually solidified and formed, and after standing in the anhydrous ethanol for 8 hours, it was placed in a vacuum drying oven at 37°C and dried for 48 hours. The vacuum degree of the vacuum drying oven was 0.01 MPa, and calcium-silicon-based bioactive silk was obtained.

[0143] Comparative Example 3

[0144] A polylactic acid filament, compared with the coaxial calcium-silicon-based bioactive filament in the embodiment, has only a core layer but no shell layer. Specifically, it is composed of a degradable polymer, and the degradable polymer is composed of polylactide with a molecular weight of 30,000 to 50,000.

[0145] The preparation method thereof comprises the following steps:

[0146] (1) Preparation of polylactide solution: 2 g of polylactide was added to 20 mL of 1,4-dioxane and stirred at 50° C. until dissolved;

[0147] (2) The polylactide solution is injected into the anhydrous ethanol coagulation bath at a rate of 100 μL / min. The polylactide solution gradually solidifies into a shape after entering the anhydrous ethanol, and is placed in the anhydrous ethanol for 8 hours and then placed in a vacuum drying oven at 37°C for 48 hours with a vacuum degree of 0.01 MPa to obtain polylactic acid filaments.

[0148] Comparative Example 4

[0149] A calcium-silicon-based bioactive filament, which differs from the coaxial calcium-silicon-based bioactive filament of Example 6 only in structure and preparation method, and the preparation method comprises the following steps:

[0150] (1) Preparation of polylactide solution: 2 g of polylactide was added to 20 mL of 1,4-dioxane and stirred at 50° C. until dissolved;

[0151] (2) Preparation of carboxymethyl chitosan solution containing 45S5 particles: 5 g of carboxymethyl chitosan was added to 20 mL of water and stirred at room temperature until completely dissolved, and then 0.05 g of bioactive glass 45S5 particles with a particle size of 20 to 500 nm were added and stirred to mix evenly;

[0152] (3) Preparing a mixed spinning solution: pour the solution in step (2) into the solution in step (1), stir and mix evenly, inject into an anhydrous ethanol coagulation bath at a rate of 90 μL / min to solidify and form, let stand in anhydrous ethanol for 8 hours, then put into a vacuum drying oven at 37°C and dry for 48 hours. The vacuum degree of the vacuum drying oven is 0.01 MPa to obtain calcium-silicon-based bioactive filaments.

[0153] Table 1 Parameters of coaxial regenerated silicon bioactive wires in various embodiments

[0154] project Wire diameter (μm) Core diameter (μm) Shell thickness (μm) Tensile strength(MPa) Example 1 245±5 205±2 40±2 71 Example 2 243±5 198±2 45±2 180 Example 3 605±5 565±2 47±2 206 Example 4 295±5 215±2 80±2 63 Example 5 250±5 208±2 42±2 103 Example 6 233±5 194±2 39±2 69 Example 7 189±5 155±2 34±2 57 Example 8 226±5 201±2 25±2 67 Example 9 8.85±0.5 6±0.5 2.85±0.05 3 Example 10 985±5 750±0.5 235±0.5 325 Comparative Example 1 213±2 205±2 8±2 65 Comparative Example 2 42±2 - 42±2 25 Comparative Example 3 205±5 205±5 - 62 Comparative Example 4 233±5 - - 38

[0155] As can be seen from Table 1, the tensile strength of a single wire obtained in Examples 1-10 is between 3 and 325 MPa, and the wires can be used in the fields of absorbable surgical sutures, bone filling, wound dressings or anti-adhesion membranes in a single or multiple strands according to the requirements of mechanical properties. For example, wires above 60 MPa can be used to make absorbable surgical sutures, wires above 100 MPa can be used as wires for fixation in bone filling applications, and wires greater than 25 MPa can be used to make wound dressings and anti-adhesion membranes and are used in the fields of wound repair and postoperative anti-adhesion, respectively.

[0156] Furthermore, by comparing Examples 1 and 2, it can be seen that when the polymer concentration, natural biomaterial matrix concentration, calcium-silicon-based bioactive material content, core and shell solution flow rates, and filament diameter, core layer diameter and shell layer thickness are all equivalent, the tensile strength of Example 2 is significantly higher than the tensile strength of Example 1. This is because the molecular weight of the core layer polymer is the main factor affecting the mechanical properties. When the polymer concentration is the same, the shell layer composition is the same and the core and shell sizes are equivalent, the higher the polymer molecular weight, the higher the tensile strength of the filament.

[0157] By comparing Examples 1 and 3, it can be seen that when the polymer molecular weight, natural biomaterial matrix concentration, calcium-silicon-based bioactive material content, and core layer and shell layer solution flow rates are all equivalent, the tensile strength of Example 3 is significantly higher than that of Example 1. This is because the polymer concentration of Example 3 is high and the core layer diameter and the wire diameter are large. Therefore, it can be seen that when the polymer molecular weight is the same, the shell layer composition is the same, and the shell layer size is equivalent, the higher the polymer concentration, the larger the core layer diameter and the wire diameter, the higher the tensile strength of the wire.

[0158] By comparing Examples 1 and 4, it can be seen that when the composition of the core layer is the same and the diameter is comparable, the tensile strength of Example 1 with a low recycled silicon content and a thin shell layer is higher than the tensile strength of Example 4 with a high recycled silicon content and a thick shell layer. This is because the content of active particles in the shell layer affects the mechanical properties of the shell layer. The higher the content, the worse the mechanical properties, which will also affect the overall mechanical properties of the wire.

[0159] By comparing Examples 1 and 5, it can be seen that when the polymer molecular weight and the core-shell material concentration are the same and the wire diameter, core layer diameter and shell layer thickness are all equivalent, the tensile strength of Example 5 is higher than that of Example 1. This is because the bonding force between the shell layer and the core layer will also affect the overall mechanical properties, and dopamine has stronger adhesion than carboxymethyl chitosan. Therefore, the bonding force between the shell layer containing dopamine and the core layer is strong, and the overall mechanical properties of the wire are strong.

[0160] By comparing Examples 1 and 7, it can be seen that the faster the injection speed of the core layer solution, the smaller the core layer diameter, the smaller the tensile strength, and the thickness of the shell layer. It may be that when the injection speed of the core layer solution is fast, the shell layer is stretched and becomes thinner.

[0161] By comparing Examples 1 and 8, it can be seen that the injection speed of the shell solution has little effect on the core layer diameter and tensile strength, but has a certain effect on the shell thickness. Although a slow shell speed can better stay and diffuse in the solution, the slower the shell solution injection speed, the greater the speed difference with the core layer solution, and the stretching effect makes the shell thickness smaller.

[0162] By comparing the shell thickness of Example 8 with that of Comparative Example 1, it can be seen that the effect of using anhydrous ethanol as a coagulant is far better than that of water as a coagulant. The anhydrous ethanol coagulant can well maintain the shape of the coaxial fiber, so that the shell layer is well coagulated and attached to the core layer.

[0163] By comparing the tensile strength of Examples 1 to 3 with that of Comparative Example 2, it can be seen that the degradable polymer core layer can provide mechanical support for the calcium-silicon-based bioactive material shell layer, thereby solving the problem of poor mechanical properties of calcium-silicon-based bioactive material fiber filaments.

[0164] By comparing the tensile strength of Examples 1, 4, 6, and 8 with that of Comparative Example 3, it can be seen that quantitatively distributing the calcium-silicon-based bioactive material on the surface of the degradable polymer to form a coaxial wire structure with a shell layer covering a core layer will not destroy the mechanical properties of the polymer wire. The coaxial calcium-silicon-based bioactive wire with a shell layer covering a core layer has excellent tensile strength and flexibility.

[0165] By comparing the tensile strength of Example 6 with that of Comparative Example 4, it can be seen that the coaxial filaments in the present invention, in which the calcium-silicon-based bioactive material is quantitatively distributed on the surface of the degradable polymer to form a shell-coated core structure, have a strength much higher than that of the conventional filaments obtained by electrospinning by mixing the calcium-silicon-based bioactive material into the degradable polymer spinning solution.

[0166] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A coaxial calcium-silicon-based bioactive wire, characterized in that: The coaxial calcium-silicon-based bioactive filament comprises: a degradable polymer core layer and a calcium-silicon-based bioactive material shell layer, wherein the calcium-silicon-based bioactive material shell layer contains a natural biomaterial matrix and calcium-silicon-based bioactive material particles, and the natural biomaterial matrix is ​​composed of one or more of natural polysaccharides and dopamine.

2. The coaxial calcium-silicon-based bioactive filament according to claim 1, characterized in that: The degradable polymer core layer is composed of one or more of polylactide, polyglycolide-lactide copolymer, polycaprolactone, polyglycolic acid, polyvinyl alcohol, and polyhydroxyalkanoate; and / or, the molecular weight of the degradable polymer used in the degradable polymer core layer is 10,000 to 150,000; And / or, the natural polysaccharide includes cellulose, chitin, chitosan, chondroitin sulfate, and seaweed polysaccharide; And / or, the calcium-silicon-based bioactive material particles are composed of one or more of bioactive ceramics, bioactive glass, regenerated silicon, calcium phosphosilicate and their derivatives.

3. The coaxial calcium-silicon-based bioactive filament according to claim 1, characterized in that: The diameter of the degradable polymer core layer is 1 μm to 1 mm; and / or, the thickness of the calcium-silicon-based bioactive material shell layer is 500 nm to 500 μm; And / or, in the calcium-silicon-based bioactive material shell layer, the mass percentage of calcium-silicon-based bioactive material particles is 0.1% to 60%.

4. The coaxial calcium-silicon-based bioactive filament according to claim 3, characterized in that: The diameter of the degradable polymer core layer is 5 μm to 760 μm; And / or, the thickness of the calcium-silicon-based bioactive material shell layer is 800nm ​​to 250μm; And / or, in the calcium-silicon-based bioactive material shell layer, the mass percentage of calcium-silicon-based bioactive material particles is 1% to 35%.

5. A method for preparing the coaxial calcium-silicon-based bioactive wire according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) preparing a degradable polymer core layer solution: dissolving a degradable polymer in an organic solvent and mixing the mixture uniformly to obtain the degradable polymer core layer solution; (2) preparing a shell solution containing calcium-silicon-based bioactive material particles: first dissolving a natural biomaterial matrix in a suitable solvent, mixing uniformly, to obtain a natural biomaterial matrix solution, then adding calcium-silicon-based bioactive material particles to the natural biomaterial matrix solution, mixing uniformly, to obtain the shell solution containing calcium-silicon-based bioactive material particles; (3) The degradable polymer core layer solution obtained in step (1) and the shell layer solution containing calcium-silicon-based bioactive material particles obtained in step (2) are respectively injected into a core layer solution syringe and a shell layer solution syringe, and coaxial wet spinning is performed with the aid of a coaxial needle, and then anhydrous ethanol is selected as a coagulation bath and / or drying is performed for solidification to obtain the calcium-silicon-based bioactive filament.

6. The preparation method according to claim 5, characterized in that: The concentration of the degradable polymer core layer solution in step (1) is 0.05 g / mL to 0.50 g / mL; and / or, the concentration of the natural biomaterial matrix solution in step (2) is 0.025 g / mL to 1.50 g / mL; And / or, the particle size of the calcium-silicon-based bioactive material particles in step (2) is 20 nm to 80 μm.

7. The preparation method according to claim 6, characterized in that: The concentration of the degradable polymer core layer solution in step (1) is 0.05 g / mL to 0.40 g / mL; and / or, the concentration of the natural biomaterial matrix solution in step (2) is 0.025 g / mL to 1.20 g / mL; And / or, the particle size of the calcium-silicon-based bioactive material particles in step (2) is 20 nm to 50 μm.

8. The preparation method according to claim 5, characterized in that: The organic solvent in step (1) is one or a mixture of ethyl acetate, dichloromethane, acetone, 1,4-dioxane, N-methylpyrrolidone, chloroform, tetrahydrofuran, hexafluoroisopropanol, acetonitrile and dichloroacetic acid; And / or, the coaxial wet spinning technology in step (3) is to inject the degradable polymer core layer solution and the shell layer solution containing calcium-silicon-based bioactive material particles through an injection head to obtain the coaxial calcium-silicon-based bioactive filament structure, and the injection head is a coaxial needle having a coaxially arranged inner channel and outer channel.

9. The preparation method according to claim 8, characterized in that: The degradable polymer core layer solution is injected at an injection speed of 40 μL / min to 10 mL / min; further, the injection speed of the degradable polymer core layer solution is 100 μL / min to 6 mL / min; And / or, the shell solution containing calcium-silicon-based bioactive material particles is injected at an injection speed of 10 μL / min to 5 mL / min; further, the shell solution containing calcium-silicon-based bioactive material particles is injected at an injection speed of 40 μL / min to 2 mL / min; And / or, the drying temperature in step (3) is 35°C to 45°C; further, the drying temperature is 35°C to 40°C; And / or, the drying in step (3) is vacuum drying, the vacuum drying time is 8h to 72h, and the vacuum degree is -0.1MPa to 0.1MPa; further, the vacuum drying time is 12h to 48h, and the vacuum degree is -0.08MPa to 0.06MPa.

10. Use of the axolotl-based bioactive filaments prepared by the preparation method of the axolotl-based bioactive filaments according to any one of claims 1 to 4 or any one of claims 5 to 9 in the fields of absorbable surgical sutures, bone fillings, wound dressings, and anti-adhesion membranes.

Citation Information

Patent Citations

  • Formula and preparation method of POSS-based regenerative medical material

    CN109771692A

  • A biodegradable regenerative medical material that promotes in-situ tissue regeneration and its preparation method

    CN110101904B

  • Bioactive silicon regenerative medical material and preparation method thereof

    CN111017934A

  • Polymer matrix composite membrane with high energy density and preparation method thereof

    CN102504449A

  • Chitin whisker / magnesium oxide whisker / biodegradable polyester composite material as well as preparation method and application thereof

    CN105504715A